Performance Analysis of Two Different Pulses with SNR for UWB Indoor Localization - Mohanty, Sujata; Tripathy, Aruna; Pradhan, Sonali (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Localization is the technique which is commonly employed in wireless network to improve routing and enhance the security. It is the method of determining the position of the object, people, and equipment etc. It has a varieties of applications in different Indoor area system like: In Millitary, Shopping center, Museums, Health care system, In IOT etc. The ultra-wideband (UWB) plays a crucial role in the field of localization for its several features like wide range of frequency (3.1GHz-10.6GHz), ability of penetration to the barriers, ranging accuracy is high (cm), capable of avoiding the multipath fading etc. Indoor positioning system (IPS) using UWB signal provides accurate and real time positioning of the person or any target node device in the area of localization. The UWB transmission scheme proposed two major approaches that are single band approach and multiband approach. For designing the UWB pulses, it is very important to consider the shape of the pulse along with spectral mask which should satisfy the FCC mask spectrum for UWB system. The study of basic pulse shape is very important, because the performance of UWB technology strictly depends on it, like efficient and reliable use of emission power, existing with other radio technology etc. The basic pulses used for simulation of this paper are Gaussian pulse and rectangular pulse. Here in this paper, the two pulses (Gaussian and Rectangular) and SNR values are taken into consideration for IPS. Both these two received pulses undergo the operation of averaging and correlation with that of the original transmitted signal for getting the time of arrival (TOA) data for locating the position of target in the indoor area system.